The Gene YALI0E20207g from Yarrowia lipolytica Encodes an N-Acetylglucosamine Kinase Implicated in the Regulated Expression of the Genes from the N-Acetylglucosamine Assimilatory Pathway - Flores, Carmen-Lisset (PLoS One, 2015)
The non-conventional yeast Yarrowia lipolytica possesses an ORF, YALI0E20207g, which encodes a protein with an amino acid sequence similar to hexokinases from different organisms. We have cloned that gene and determined several enzymatic properties of its encoded protein showing that it is an N-acetylglucosamine (NAGA) kinase. This conclusion was supported by the lack of growth in NAGA of a strain carrying a YALI0E20207g deletion. We named this gene YlNAG5. Expression of YlNAG5 as well as that of the genes encoding the enzymes of the NAGA catabolic pathway—identified by a BLAST search—was induced by this sugar. Deletion of YlNAG5 rendered that expression independent of the presence of NAGA in the medium and reintroduction of the gene restored the inducibility, indicating that YlNag5 participates in the transcriptional regulation of the NAGA assimilatory pathway genes. Expression of YlNAG5 was increased during sporulation and homozygous Ylnag5/Ylnag5 diploid strains sporulated very poorly as compared with a wild type isogenic control strain pointing to a participation of the protein in the process. Overexpression of YlNAG5 allowed growth in glucose of an Ylhxk1glk1 double mutant and produced, in a wild type background, aberrant morphologies in different media. Expression of the gene in a Saccharomyces cerevisiae hxk1 hxk2 glk1 triple mutant restored ability to grow in glucose.